PENGARUH LIKUIDITAS, PROFITABILITAS, DAN STUKTUR MODAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MAKANAN & MINUMAN DI BURSA EFEK INDONESIA PERIODE 2016-2022 - Ranti Anggraini (2022)
The Impact of Liquidity, Profitability, and Capital Structure on Firm Value in Foods and Beverages Company at Indonesia Stock Exchange 2016-2020 Period By Ranti Anggaraini Abstract The purpose of this study was to determine the effect of liquidity, profitability, and capital structure on food and beverage companies on the Indonesia Stock Exchange for the 2016-2020 period. The sample used is 14 food and beverage companies and the overall data is processed using panel data regression. The results of this study indicate that liquidity and capital structure have no effect on the profitability of food and beverage companies. Other results obtained that liquidity has no effect on firm value, while capital structure and profitability have a positive and significant effect on firm value. Profitability in this study cannot mediate the effect of liquidity and capital structure on firm value. Keyword: Liquidity, Firm Value, Profitability, Capital Structure, Foods and Beverage Company